A comparison of methods to estimate genomic relationships using pedigree and markers in livestock populations. (2nd May 2016) - Forneris, N.S.; Steibel, J.P.; Legarra, A.; Vitezica, Z.G.; Bates, R.O.; Ernst, C.W.; Basso, A.L.; Cantet, R.J.C.
Summary: Accurate prediction of breeding values depends on capturing the variability in genome sharing of relatives with the same pedigree relationship. Here, we compare two approaches to set up genomic relationship matrices for precision of genomic relationships (GR) and accuracy of estimated breeding values (GEBV). Real and simulated data (pigs, 60k SNP) were analysed, and GR were estimated using two approaches: (i) identity by state, corrected with either the observed ( G VR ‐O ) or the base population ( G VR ‐B ) allele frequencies and (ii) identity by descent using linkage analysis ( G IBD ‐L ). Estimators were evaluated for precision and empirical bias with respect to true pedigree IBD GR. All three estimators had very low bias. G IBD ‐L displayed the lowest sampling error and the highest correlation with true genome‐shared values. G VR ‐B approximated G IBD ‐L 's correlation and had lower error than G VR ‐O . Accuracy of GEBV for selection candidates was significantly higher when G IBD ‐L was used and identical between G VR ‐O and G VR ‐B . In real data, G IBD ‐L 's sampling standard deviation was the closest to the theoretical value for each pedigree relationship. Use of pedigree to calculate GR improved the precision of estimates and the accuracy of GEBV.